Pengembangan Aplikasi Database Analisa Penjualan pada Perusahaan Maju Makmur - Priatna, Alifiya Meiliza Putri; Calulla Nur, Alfiah; Aziz Rizal, Abdul; Irmaniansyah, Dhony; Pramudito, Titah; Hariyadi, Gerald (Jurnal Sains Indonesia, 2023)
The creation of this database was carried out to develop a sales recording system for salesmen who handle different branches. A Microsoft Access-based database, of course, has primary key components in unique data that will be linked from one table to another. Based on the primary key for each entity, a relationship between data will be formed that will automatically function in various processes, such as making queries to reports. These components will produce an ERC (Entity Relationship Chart) which describes the logic of the database by showing the relationships between entities and their attributes in full. This database will reveal the salesman's ranking including the number of sales and total outlet receipts with accurate and reliable data. The creation of this database is expected to be able to help the Maju Makmur Company on an ongoing basis so that the performance appraisal decision process will be more effective and efficient.